AN ANALYSIS OF THE IMPLEMENTATION OF CHARACTER EDUCATION POLICY IN SCHOOL TO MEET THE ASEAN ECONOMIC COMMUNITY (An Expectation and Challenge) - Trisiana, Anita (PROCEEDING INTERNASIONAL SEMINAR, 2015)
One of the global symptoms is the increasing of people migration intensity from one area to another. People like this are no longer constrained by the country territory, ethnic group, or religion or identity. This is different from citizenship where national citizenship rights are based on geographical boundaries of existing laws and procedures so that it can determine who can become the members of the nation. Today the idea of global citizenship has emerged. Besides, global citizenship is not something tangible but rather a moral or ethical stance on the need for protection of the rights of citizens in a global context. In order to meet the Asean Community, in the global context, a citizen has an important role to be a good citizen who can participate in implementing public policy. Character education, one of government policies, needs to be applied. Along with the grand design of the implementation of character education, it is not only done within the family, but also in the community, and education units. In units of education, especially in schools, character education forms an expectation and a challenge to be able to be applied effectively as one pillar and supporter of the Asean Community in line with the principles of global citizenship.